The Coumarins: Secondary Metabolites Playing a Primary Role in Plant Nutrition and Health. (March 2021) - Robe, Kevin; Izquierdo, Esther; Vignols, Florence; Rouached, Hatem; Dubos, Christian
Abstract : Although abundant in soils, iron (Fe) is poorly bioavailable for plants. Improving Fe uptake in crops, enabling them to grow in Fe-depleted soils, has become a major focal interest. The secretion of Fe-mobilizing coumarins by plant roots recently emerged as an important factor allowing nongrass species to cope with low Fe bioavailability. The main molecular actors involved in the biosynthesis and secretion of coumarins have been identified, but the precise regulatory mechanisms that tune their production remain poorly understood. Here, we review the recent progress in coumarin synthesis and transport in plants and future research directions to gain knowledge of these mechanisms, which will offer novel opportunities for improving plant growth and health and for generating Fe-fortified crops. Highlights: Iron is an important factor conditioning biomass production, crop yield, and the quality of plant products. Although iron is the fourth most abundant element on Earth, iron is poorly available for plants. The secretion of coumarins is a crucial mechanism for iron uptake in nongrass species when iron availability is low, particularly in alkaline soils. Recent studies have identified the main coumarins involved in iron uptake and the main biochemical steps and regulatory processes controlling their biosynthesis. These findings provide novel targets for improving plant growth and health together with iron content in the edible part of plants and thus human diet.